The Influence of Social Media and Promotion on Purchase Intention Mediated By Brand Image In Lukisan Bumi Restaurants In Yogyakarta (Empirical Study: Consumers of Lukisan Bumi Restaurants In Yogyakarta) - Dohardo Roma; Liem Bambang Sugiyanto (Publikasi Indonesia, 2024)
The purpose of this study was to determine the effect of social media and promotion on purchase intention, and to determine the role of brand image as a mediating variable for consumers at Lukisan Bumi Restaurant in Yogyakarta. This research can be conducted using online and offline methods to 140 respondents with the criteria of being consumers of the Earth Painting Restaurant in Yogyakarta. This study uses a quantitative approach using structural equation models and is processed using the AMOS 24 program. The results of this study indicate that social media and promotion has positive and significant affect to purchase intention on Lukisan Bumi Restaurant consumers at Yogyakarta. This research also show that social media and promotion has positive affect to purchase intention mediated by brand image. The result this research that both of independent variable and mediating variable effectively enhance the purchase intention Restoran Lukisan Bumi consumers. Limit of this research is a survey conducted on consumers of the Earth Painting Restaurant in Yogyakarta and the survey period was only carried out for one month, and the respondents in this study were only consumers who live in Yogyakarta. The implication of this research is interaction analyst among variables social media, promotion, brand image, and purchase intention. This study seeks to understand social media could promoting Lukisan Bumi Restaurant for affect purchase intention. The result this research hoped provide knowledge to marketers and manufacturer to design effective social media and promotion strategy for increase consumers purchase intention.